Teachers stepping up their game in the face of extreme statements: A qualitative analysis of educational friction when teaching sensitive topics - Lozano Parra, Saro; Wansink, Bjorn; Bakker, Cok; van Liere, Lucien (Taylor and Francis, 2023)
Friction in the classroom may create useful tension for teachers when they attempt to discuss sensitive topics as part of democratic learning. Due to the openness and indeterminacy of these topics, students can experience what it is like to be (political) subjects in a diverse society and become aware of other people’s subjectness in a charged classroom. To better understand how to handle educational friction in the classroom, we observed and interviewed nine Dutch expert teachers and analyzed the empirical data by using our Educational Friction Modelling Framework as a heuristic lens. This study shows how teachers allowed extreme statements and used the subsequent friction during their lessons, challenged and provoked their students, made room for their pupils in several ways to enhance their participation, and made a distinction between rationality and emotions in the classroom. We argue that our framework sheds light on what charges the classroom and contributes to the further development of contained risk-taking as part of democratic education.
Keywords: Democratic learning; friction; multiperspectivity; narrativity; playground; sensitive topics; Education; Sociology and Political Science